Managerial accounting activities - Hannon, Neal J. (Cincinnati, OH : South-Western College, 2000)
This book is about: Allocation of costs; Standard costs and job orde costing; Operationak budgets; Divisional performance; Inventory management; ...
Keywords: Accounting; Managerial accounting; Managerial economics -- Case studies